A Bias in the Reading of the Genetic Code of Escherichia coli is a Characteristic for Genes that Specify Stress-induced MazF-mediated Proteins - Nigam, Akanksha; Oron-Gottesman, Adi; Engelberg-Kulka, Hanna (Current Genomics, 2020)
Background: Escherichia coli (E. coli) mazEF, a stress-induced toxin-antitoxin (TA) system, has been studied extensively. The MazF toxin is an endoribonuclease that cleaves RNAs at ACA sites. Thereby, under stress, the induced MazF generates a Stress-induced Translation Machinery (STM), composed of MazF processed mRNAs and selective ribosomes that specifically translate the processed mRNAs. Materials and Methods: Based on the data from the EcoCyc website of the National Center for Biotechnology Information (NCBI), the sequence of all E. coli MG1655 genes were scanned for ACA sites upstream from the initiation codons. Among these sequences, the fuzznuc program of the
Keywords: genes